2019
DOI: 10.1016/j.cell.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

TNF Induces Pathogenic Programmed Macrophage Necrosis in Tuberculosis through a Mitochondrial-Lysosomal-Endoplasmic Reticulum Circuit

Abstract: SummaryNecrosis of infected macrophages constitutes a critical pathogenetic event in tuberculosis by releasing mycobacteria into the growth-permissive extracellular environment. In zebrafish infected with Mycobacterium marinum or Mycobacterium tuberculosis, excess tumor necrosis factor triggers programmed necrosis of infected macrophages through the production of mitochondrial reactive oxygen species (ROS) and the participation of cyclophilin D, a component of the mitochondrial permeability transition pore. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
190
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(208 citation statements)
references
References 107 publications
(182 reference statements)
10
190
0
Order By: Relevance
“…The role of necroptosis, a form of programmed necrotic cell death, remains controversial in TB (Pajuelo et al, 2018;Stutz et al, 2018a;Stutz et al, 2018b;Zhao et al, 2017). TNF-related cell necrosis was reported in Mycobacterium marinum-infected zebrafish in vivo and M. marinum-infected macrophage cell lines in vitro without conforming to the current model of necroptosis (Roca et al, 2019), but that study did not involve Mtb or primary mammalian macrophages. Pyroptosis, a form of programmed necrotic cell death mediated by gasdermin proteins (Kayagaki et al, 2015;Shi et al, 2017;Shi et al, 2015;Wang et al, 2017), usually involves inflammasome activation and the maturation and release of pro-inflammatory cytokines, including IL-1β.…”
Section: Introductionmentioning
confidence: 92%
“…The role of necroptosis, a form of programmed necrotic cell death, remains controversial in TB (Pajuelo et al, 2018;Stutz et al, 2018a;Stutz et al, 2018b;Zhao et al, 2017). TNF-related cell necrosis was reported in Mycobacterium marinum-infected zebrafish in vivo and M. marinum-infected macrophage cell lines in vitro without conforming to the current model of necroptosis (Roca et al, 2019), but that study did not involve Mtb or primary mammalian macrophages. Pyroptosis, a form of programmed necrotic cell death mediated by gasdermin proteins (Kayagaki et al, 2015;Shi et al, 2017;Shi et al, 2015;Wang et al, 2017), usually involves inflammasome activation and the maturation and release of pro-inflammatory cytokines, including IL-1β.…”
Section: Introductionmentioning
confidence: 92%
“…Zebrafish has been shown to be an excellent model for the study of TB [21][22][23][24][25] . Because zebrafish have large amounts of offspring at one time and the availability of high throughput automated infection methods 26 , many zebrafish larvae can be tested for TB in a short time.…”
mentioning
confidence: 99%
“…While co-injected recombinant TNF in M. marinum-infected zebrafish larvae initially reduced mycobacterial burden, macrophages underwent necroptosis (programmed necrosis) induced by a RIPK1-RIPK3-dependent mechanism, which in turn enhanced mitochondrial ROS production (64). Exploiting the relative ease of exposing larval zebrafish to chemical inhibitors, it was shown that two pathways cooperate to induce this ROS-dependent macrophage necrosis via an inter-organellar circuit (65). Initially, mitochondrial ROS activates ceramide production via the lysosomal enzyme acid sphingomyelinase (aSM).…”
Section: The Macrophage Response To Mycobacterium Marinum Is Largely mentioning
confidence: 99%